Advances in the roles and mechanisms of lignans against Alzheimer’s disease - Han, Na; Wen, Yuanyuan; Liu, Zhihui; Zhai, Jianxiu; Li, Sikai; Yin, Jun (Frontiers in Pharmacology, 2022)
Background: Alzheimer's disease (AD) is a serious neurodegenerative disease associated with memory and cognitive impairment. The occurrence of AD is due to the accumulation of amyloid beta (Aβ) plaques and neurofibrillary tangles (NFT) in the brain tissue as well as the hyperphosphorylation of Tau protein in neurons, doing harm to human health and even leading people to death. The development of neuroprotective drugs with small side effects and good efficacy is focused by scientists all over the world. Natural drugs extracted from herbs or plants have become the preferred resources for new candidate drugs. Lignans could effectively protect nerve cells and alleviate memory impairment, suggesting that they might be a prosperous class of compounds in treating AD. Objective: To explore the role and mechanism of lignans in the treatment of neurological diseases, providing proofs for the development of lignans as novel anti-AD drugs. Methods: Relevant data are collected through major scientific databases such as China National Knowledge Infrastructure (CNKI), Elsevier, Science Direct, PubMed, SpringerLink, and Web of Science. With lignan, anti-inflammatory, antioxidant, apoptosis, nerve regeneration, nerve protection as keywords, relevant literature was extracted and retrieved from the above database. Results: The existing research progress was summarized, and lignans were found to have the effects of anti-inflammation, anti-oxidation, anti-apoptosis, improving intestinal flora, promoting nerve regeneration so as to strengthening nerve protection. Conclusion: Lignans are promising natural neuroprotectants. This review will contribute to the future development of lignan as new clinical candidates for the treatment of neurological diseases.